Mejoras de eficiencia energética en calefacción. Potencial de intervención en edificio escolar existente del área Metropolitana de San Juan, Argentina - Ré, María Guillermina (Universidad del Bío-Bío, Chile, 2021)
Climate change, the constant growth of energy consumption, and the high levels of emissions recorded by the energy sector, require the implementation of concrete solutions. Building rehabilitation offers a significant opportunity to contribute in this regard. The purpose of this work is to analyze the potential for intervention in a school building from the “Programa Nacional 700 Escuela” (National 700 Schools Program). The improvements in energy efficiency are evaluated through a dynamic simulation and indicators are calculated regarding the annual energy consumption for heating. The values for the reference building are 74.5 kWh/m2 year and 158 kWh/student. With the rehabilitation proposals, energy savings could be achieved of between 39.7% and 60%. The R-Mean alternative appears as the most convenient one as it achieves energy benefits of 47%, with lower investment costs. The energy efficiency indicators for said set of improvements are 39.2 kWh/m2 year and 83.1 kWh/student. The results achieved can serve as reference for the rehabilitation of 71 school buildings built in the province of San Juan between 2004 and 2015, which belong to a construction typology with a similarity of materials of their envelope and functional configuration.